Culture-led urban regeneration: The case of Maboneng - Meek, Louise Gardner (Department of Civil Engineering, 2017)
This dissertation utilizes a case study of Maboneng in Johannesburg central business district (CBD) to make a case for culture-led urban regeneration in South Africa. The City of Johannesburg is still to a large extent locked into Apartheid-era spatial planning whereby most neighbourhoods' reflect the Group Areas Act's racial profiles of the past. Given this historical context, a more nuanced approach to culture-led regeneration is required in assessing the complexity of urban regeneration in South Africa. This dissertation analyses to what extend Maboneng has undergone a process of culture-led urban regeneration, examining the transformation in terms of social, physical and economic outcomes. It also seeks to uncover to what extend the case of Maboneng aligns with global literature- and to what extent it departs? Chapter 2 introduces the research method, which is case study based, and relies on Propertuity company data for the purposes of this paper, which is outlined as a gap that could be addressed in a future study of the area. Chapter 3 defines culture-led urban regeneration and focuses on a literature review, with Florida's (2002) creative class theory at the core of the discussion around urban regeneration, which is critiqued by Peck (2007) who believes it leads to further prioritization of the middle class at the expense of the poor. Moulaert, Demuynck & Nussbaumer (2004) suggest a nuanced perspective to culture-led urban regeneration that adopts a socially-rooted view which values the multi dimensional role of culture in urban development. The case of Maboneng uses this nuanced perspective from the literature as a framework to categorise the data in chapter 4, and analyse the data in chapter 5, using the three dimensions of urban regeneration (namely social, physical and economic transformation) in order to assess the culture-led urban regeneration in Maboneng. The findings highlight that Maboneng is socially-rooted in its approach to both the social and economic transformations that are occurring in the neighborhood with success in the establishment of a mixed-race neighbourhood that is reflective of the City of Johannesburg racial profiles, as well as the establishment of a local economy. It is argued that more could be done to ensure the physical dimensions and aesthetics of place that are less 'curated' by the property developer and more focused on cocreation of aesthetics.